Per una "meritocrazia inclusiva", oltre le disuguaglianze sociali: il ruolo-chiave dell'educazione prescolare - Paola Caselli (Firenze University Press, 2022)
The paper focuses on the issues of merit, explored in its complex polysemy, meritocracy, and skills, placing them in relation to those of - educational, social, economic, cultural - poverty and social disadvantage, which afflict, with considerable aggravation especially in the era of Sars-Cov-2 pandemic, even Italy. The essay consists of three paragraphs. In the first two, a reference framework is outlined, on the one hand relating to the polysemic concepts of merit, and meritocracy; on the other, to the situation of poverty and social inequalities in Italy. The third paragraph, which represents the heart of the paper, is linked to the abovementioned frameworks: it highlights the key role that a widespread, accessible, and high-quality Early Childhood Education and Care (ECEC) play, both in supporting children's development, both promoting a democratic and inclusive society; a society characterized by effective "merit dynamics", open to all, so as to promote skills development and, above all, social ascent and redemption.